Analisis Kelayakan Bisnis Pada UMKM Kedai Kopi Meine Welt Di Palangka Raya - Nurlia Eka Damayanti; Deni Dwiyan Ryadi; Puja Astuti; Angelita Lavenia; Dewi Lestari; Claudia Raberta Repanela; Casma Rusmada Silaban (SANTRI : Jurnal Ekonomi dan Keuangan Islam, 2024)
In recent years, small and medium-sized enterprises operating coffee shops in the creative industry, including the Meine Welt Coffee coffee shop business, have continued to show their presence. The purpose of this study is to analyze the feasibility of a coffee shop business at the Meine Welt Coffee Shop Business and use a qualitative approach, which is a research method that produces descriptive data, to find out the expectations of a managed business if it can provide financial benefits Collected through interviews, observations, and documentation. Analysis of the feasibility of the Meine Welt coffee shop business in Palangka Raya includes a study of various aspects such as legal, environmental, market, technical, managerial, and financial aspects to determine business feasibility.